Analisis Kesalahan Kaidah Imla’ Bahasa Arab (Studi Kasus Skripsi Berbahasa Arab Mahasiswa Prodi Pendidikan Bahasa Arab FBS UNM) - Ulum, Fatkhul; Mariah, Enung; Kudus, Ruhul (Seminar Nasional LP2M UNM, 2023)
Abstract. This study analyzes the errors of Arabic writing ruler in the undergraduate thesis of students of Arabic Language Education Program (Prodi Pendidikan Bahasa Arab) at FBS UNM1. This study uses Corder’s theory of error analysis to identify, classify, describe, explain, and solve the errors of Arabic grammar2. The data of the study are qualitative data sourced from four undergraduate theses that use Arabic language. The study uses Corder’s theory of error analysis which covers six stages. The purpose of this study is to find out the types of errors of Arabic grammar in the students’ thesis and to provide solutions to overcome them. The results show that there are several types of errors of imlaiyyah rules in the students’ thesis, such as: errors in writing alif after isim isyārah and ibnu, errors in writing alif lām on al-ladzāni and al-latāni, errors in writing alif layyinah, errors in writing hamzah washal, errors in writing hamzah qath’i, errors in writing hamzah qath’i in the middle and end of words, and errors in writing al-fashl wal washlu3. The discussion of the results refers to the imlaiyyah rules that exist in the books of nahwu and sharaf and the opinions of Arabic language experts.  Kata Kunci: Error Analysis, Arabic Grammar, Undergraduate Thesis